Putting practice into words : the state of data and methods transparency in grammatical descriptions - Gawne, Lauren (2019)
Language documentation and description are closely related practices, often performed as part of the same fieldwork project on an un(der)-studied language. Research trends in recent decades have seen a great volume of publishing in regards to the methods of language documentation, however, it is not clear that linguists' awareness of the importance of robust data-collection methods is translating into transparency about those methods or data citation in resultant publications. We analyze 50 dissertations and 50 grammars from a ten-year span (2003-2012) to assess the current state of the field. Publications are critiqued on the basis of transparency of data collection methods, analysis and storage, as well as citation of primary data. While we found examples of transparent reporting in these areas, much of the surveyed research does not include key information about methodology or data. We acknowledge that descriptive linguists often practice good methodology in data collection, but as a field we need to build a better culture with regard to making this clear in research writing. Thus we conclude with suggested benchmarks for the kind of information we believe is vital for creating a rich and useful research methodology in both long and short format descriptive research writing.